2020
DOI: 10.1177/1074248420947633
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Out-of-Target LDL Cholesterol 1 to 3 Years After Myocardial Infarction. A Subanalysis From the EYESHOT Post-MI Registry

Abstract: Background: There is an incomplete understanding of the prevalence and predictors of attainment of low-density lipoprotein cholesterol (LDL-C) goal after myocardial infarction (MI). Aim: To evaluate the prevalence of achievement of LDL-C goal of 70 mg/dL, to identify the baseline features associated with suboptimal lipid control, and to assess the use of LDL-C-lowering drug therapies (LLT) beyond the first year after MI. Methods: The EYESHOT Post-MI was a prospective, cross-sectional, Italian registry, which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Most studies have focused on patients at very high, and high CV risk. Some have looked at recommendations' adherence and guideline patterns in very high-risk patients, such as those who have had a previous MI [14].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on patients at very high, and high CV risk. Some have looked at recommendations' adherence and guideline patterns in very high-risk patients, such as those who have had a previous MI [14].…”
Section: Discussionmentioning
confidence: 99%
“…Again, this more invasive and aggressive attitude may be related to the greater risk perceived by cardiologists based on the number of comorbidities rather than the number of previous MI episodes. In this regard, prior studies found incomplete prescription of recommended medications to predict re-MI [ 23 , 24 ]. In our series, about one in four patients, regardless of the number of prior MIs, was not prescribed OMT at the time of enrolment.…”
Section: Discussionmentioning
confidence: 99%
“…Landmark trials showed that LDL-c-lowering agents, such as statins and ezetimibe, significantly reduced the incidence of adverse ischemic events in patients with CAD [ 37 , 38 ]. However, several studies on lipid-lowering therapies showed a persistent residual risk of ischemic events despite an aggressive LDL-C control [ 37 , 39 , 40 ]. The issue of “residual cholesterol risk” has been partially addressed with the introduction of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors that dramatically reduce LDL-c levels when added to statin therapy, showing a significant reduction in cardiovascular events in patients with CAD [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%